1999
DOI: 10.2307/2661149
|View full text |Cite
|
Sign up to set email alerts
|

Dominant Daughters-in-Law and Submissive Mothers-in-Law? Cooperation and Conflict in South India

Abstract: The stereotype of mother-in-law and daughter-in-law relations in India is that of a dominating mother-in-law and submissive daughter-in-law. However, residents of low-income settlements in Chennai (formerly called Madras) argue that daughters-in-law no longer submit to the demands and wishes of their mothers-in-law as they do in rural Tamil Nadu, a South Indian state of which Chennai is the capital. Rather than being culturally determined, relations between mothers-in-law and daughters-in-law are shaped by shi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…Some might be explained by the much higher media attention given to cases of AIDS detected in TN in the early stages of the epidemic, but other important factors may be the greater disparities between urban and rural lifestyles, education and economic conditions in the two states. Urbanization is a powerful driver of changed family relationships: for example among low income communities in the city of Chennai (the TN state capital) there has been a redrawing of the traditional pattern of relations between mothers in law and daughters in law (Vera-Sanso, 1999). By contrast in rural TN all aspects of living conditions for the landless poor continue to be constrained by geography that determines the pattern of agriculture and seasonal employment, as well as inter-caste relations and problems in accessing safe water, food, clothing and shelter (Rajuladevi, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Some might be explained by the much higher media attention given to cases of AIDS detected in TN in the early stages of the epidemic, but other important factors may be the greater disparities between urban and rural lifestyles, education and economic conditions in the two states. Urbanization is a powerful driver of changed family relationships: for example among low income communities in the city of Chennai (the TN state capital) there has been a redrawing of the traditional pattern of relations between mothers in law and daughters in law (Vera-Sanso, 1999). By contrast in rural TN all aspects of living conditions for the landless poor continue to be constrained by geography that determines the pattern of agriculture and seasonal employment, as well as inter-caste relations and problems in accessing safe water, food, clothing and shelter (Rajuladevi, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…The younger women, in contrast, did not easily acknowledge the importance of the older women. 8,10,12,17 The influence of mothers-in-law in terms of young couples' reproductive health in South Asia is considered to be significant. Studies have reported that when mothers-in-law were not living with the couple in the same household, the probability of those couples adopting modern contraceptive methods was higher.…”
Section: Discussionmentioning
confidence: 99%
“…However, an exclusive focus on sex disparities in economic outcomes is problematic, as women’s economic empowerment is not only constrained by power relations between men and women, but also by oppression of women by women ( Cornwall, 2007 , Vera-Sanso, 2008 ). In particular, a large and well-established body of anthropological literature has analyzed the central role of intergenerational power struggles between daughters-in-law and mothers-in-law in shaping household dynamics in South Asia ( Allendorf, 2017 , Bennett, 1983 , Bennett, 1992 , Kandiyoti, 1988 , Mandelbaum, 1993 , Minturn and Kapoor, 1993 , Vera-Sanso, 1999 ). Nonetheless, relatively little of this literature has applied the lens of intergenerational power struggle to analyzing women’s economic empowerment.…”
Section: Introductionmentioning
confidence: 99%